Strategic sales leadership breakthrough thinking for breakthrough results (Thomson, 2006)
"While there are numerous cookbook approaches to sales management, very little is available on training sales leaders and managers how to think strategically and how to operate their sales teams for truly optimal results - until now. Drawing from the experiences and research of The Sales Educators' team of sales powerhouses, Strategic Sales Leadership: BREAKthrough Thinking for BREAKthrough Results delivers an